Analysis of Zakat Fitrah Pattern Distribution in Pageraji Village Cilongok District Banyumas Regency in 2020 - Siti Mu'awanah; Slamet Akhmadi (Social Science Studies, 2022)
This study discusses the Analysis of Patterns of Distribution of Zakat Fitrah in Pageraji Village, Cilongok District, Banyumas Regency in 2020. This research was conducted because the distribution of zakat fitrah in Pageraji Village, Cilongok District, Banyumas Regency is still given to those who are not entitled to receive it. Therefore, the author wants to examine how to analyze the pattern of distribution of zakat fitrah in Pageraji Village, Cilongok District, Banyumas Regency. The formulation of the problem is a) How are the efforts made by the people of Pageraji Village, Cilongok District, Banyumas Regency in the implementation of zakat fitrah? b) How is the analysis of the distribution pattern of zakat fitrah in Pageraji Village, Cilongok District, Banyumas Regency in 2020? This study aims to a) To explain the causes of zakat fitrah must be managed properly. b) To analyze the distribution pattern of zakat fitrah in Pageraji Village, Cilongok District, Banyumas Regency in 2020. This study uses qualitative research with field research, where the author goes directly to the community, both muzakki, amil, and mustahik in Pageraji Village, Cilongok District, Banyumas Regency. The approach used is a case study approach. Then check the validity of the data using the triangulation method. The results of the study indicate that the implementation of zakat fitrah collection in Pageraji Village, Cilongok District, Banyumas Regency in 2020 is divided into 4 ways, namely through mosques, through Koran teachers, through RT and distributed directly to relatives, relatives, relatives or neighbors. Zakat fitrah collected is distributed or distributed to people who are entitled to receive or group 8 asnaf using consumptive patterns or temporary assistance. This is also done by muzakki who distribute their zakat fitrah directly to mustahik. However, in the implementation of the distribution of zakat fitrah, there are still mustahik who are not entitled to receive it, namely rich widows or widowers.